The Quality of Service Affect Loyalty Through Customer Satisfaction as Intervening Variables in Indonesian Zalora - Wiludjeng Sunu Purwaningdyah, Sri; Haizam Mohd Saudi, Mohd; Maya Dora, Yenny; Martri, Dwinto (International Journal of Engineering and Technology, 2018)
Zalora Indonesia is one of the biggest fashion online shopping centers in Indonesia that provides men's and women's fashion needs. The company strives to satisfy its customers by improving service quality, but there are still complaints experienced by Zalora Indonesia customers. This makes the authors interested in examining the ability of service quality to influence consumer loyalty through satisfaction as an intervening variable in Zalora Indonesia consumers (Online Business Studies in Zalora Indonesia). The purpose of the study was to determine the influence of service quality on customer satisfaction and consumer loyalty. The samples taken were Zalora consumers using accidental sampling techniques. The tools used are simple regression and hierarchical regression. The results showed that service quality influences customer satisfaction positively and significantly, satisfaction was also influences loyalty significantly, and service quality was able to influence loyalty, but was not mediated by satisfaction (Z) as an intervening variable in Zalora Indonesia.Â Â